The influence of work culture, leadership style, and remuneration on employee performance within the regional secretariat of East Java Province - Purwaningsih, Heni; Rahayu, Sri; Sundjoto, Sundjoto (Universitas Wiralodra, 2024)
This study aims to analyze the influence of work culture, leadership style, and remuneration on employee performance within the Regional Secretariat of East Java Province. This research adopts a quantitative approach, which focuses on the measurement and analysis of numerical data. This approach tends to utilize structured data collection instruments, such as questionnaires or surveys, to gather data from respondents. The research findings indicate that a positive work culture, effective leadership style, and fair remuneration system have a significant positive impact on employee performance. These findings provide insights for organizations to enhance working conditions and employee satisfaction, ultimately strengthening overall organizational performance. Managerial implications include the need for a supportive work culture, the implementation of motivating leadership styles, and a transparent remuneration system. This study contributes to understanding the factors influencing employee performance in the context of the public sector, particularly within the Regional Secretariat of East Java Province.